Renesans baśni - Gieba, Kamila (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article’s aim is is to reviw two-volume monograph entitled Fairy tale in Contemporary Cultre edited by Kornelia Ćwiklak (volume 1: Fairy tale’s limitless potential: literature – art – mass culture , volume 2: The human realm: education – psychoanalisys – art therapy ). Reviewed publication presents theoretical proposals and interpretations of cultural texts related to the fairy tales.